Peran Guru PAI terhadap Keaktifan Siswa Tahfidz di MI Miftahul Afkar Bumiayu - Sita Anggia Kusuma; Aulia Nur FarahDillah (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study examines the role of Islamic Religious Education (PAI) teachers in enhancing student activeness within the tahfidz program under the Full Day School system at MI Miftahul Afkar Bumiayu in the 2025/2026 academic year. The research was motivated by the varying levels of student participation during tahfidz learning activities despite the intensive learning environment provided by the Full Day School system. This study employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that PAI teachers play significant roles as educators, motivators, facilitators, and evaluators in improving students’ physical, mental, and emotional activeness during tahfidz learning. Teachers applied various learning methods such as murāja’ah, talaqqi, memorization deposits, educational games, question-and-answer sessions, and digital media to create an interactive and enjoyable learning atmosphere. Supporting factors included a religious school environment, adequate learning facilities, the structured Full Day School program, and collaboration between teachers and parents. Meanwhile, inhibiting factors included students’ physical fatigue, differences in memorization abilities, limited murāja’ah time at home, and learning boredom due to long study hours. Therefore, the success of the tahfidz program in the Full Day School system is strongly influenced by the ability of PAI teachers to manage active, innovative, and student-centered learning.